Gambaran Strategi Program Studi Keperawatan Untuk Meningkatkan Kelulusan Mahasiswa Dalam Uji Kompetensi : Literatur Review - Ahmad Mushawwir; Takdir Tahir; Kusrini Kadar; Hamdiah Ahmar; Nur Khalid (Jurnal Keperawatan Muhammadiyah, 2019)
Description departement of nursing strategy to increase students approach in competency test: literatur review  AbstractBackground: Nursing competency exam is a process to measure the knowledge, skills and performance of student in colleges that obtaining nursing department which aimed to achieve the standard of competency of alumnae who meet up with work proficiency standard. The nursing competency exam has been conceded by twelve times in Indonesia, with the National UKNI results by period VII was 37.87%, in period VIII was 37.42%, on period IX was 33.46% and on period X was 39,3%. The results show how pure the passing grad rate of students in UKNI. Methods: the databases used in this literature are Pubmed, Science Direct, and Wiley online. Result: There were 14 articles, but those who comply with the inclusion criteria were 7 articles. Some studies show a number of institutional strategies to improve student passing grade in NCLEX-RN competence exam. Discussion : online caching, nursing clinic courses, remedial policies, fourteen steps Exit Examination Review, a course in focusing to solving clinical decision problems, preparation competency test courses, course work and Adaptive Quizzing System tests, the  educational basic curriculum establishment, learning methods, the students risk Adaptive Quizzing program detection, learning style, confidence and Locus of Control (LOC) as some strategi of institution to improve student passing grade in NCLEX-RN competence exam. Conclusion: to increase the percentage of student graduation in the competency test it takes the seriousness of the institution to foster and prepare students to take the competency test.